Efektivitas Air Rebusan Daun Binahong (Anredera cordifolia) Terhadap Pertumbuhan Salmonella typhi - Ratih Dewi Dwiyanti; Nurlailah Nurlailah; Indah Kurnia Widiningsih (Medical Laboratory Technology Journal, 2015)
Typhus is one of acute febrile illness caused by the bacterium Salmonella typhi. Treatment of typhoid fever usually use antibiotics, the use of antibiotics can cause side effects. People today are using treatment with natural ingredients, one of which is Binahong (Anredera cordifolia) compounds containing alkaloids, polyphenols, flavonoids, saponin, and anthraquinone is efficacious as an antibacterial. This study aims to determine the effectiveness of the water decoction of leaves Binahong against Salmonella typhi growth in vitro. This type of research is true experiment with posttest study design Only Control Group Design and methods used are diffusion (wells) with 5 treatment. The concentration of the cooking water leaves the dgunakan Binahong is 20%, 40%, 60%, 80% and 100%. The result showed inhibition zone water decoction of the leaves Binahong against Salmonella typhi at a concentration of 20%, 40%, 60%, 80% is 0 mm, whereas at 100% concentration obtained inhibition zone of 11 mm. It is concluded that the water decoction of the leaves Binahong at a concentration of 100% has the ability to inhibit the growth of Salmonella typhi, but these results have not been effective because it is still in the category of resistance. It is suggested for further research to increase the concentration of water decoction of the leaves binahong or use alcohol extract of leaves binahong to inhibit the growth of Salmonella typhi.